Investigation into the thermodynamics and kinetics of the binding of Cu2+ and Pb2+ to TiS2 nanoparticles synthesized using a solvothermal process. Issue 6 (December 2019) - Cantu, Jesus; Valle, John; Flores, Kenneth; Gonzalez, Diego; Valdes, Carolina; Lopez, Jorge; Padilla, Victoria; Alcoutlabi, Mataz; Parsons, Jason
Highlights: A TiS2 nanomaterial was synthesized through a solvothermal process. The binding of Cu2+ and Pb2+ions from aqueous solution to the TiS2 was pH dependent. Lead bound by chemisorption copper bound by a combination of chemi/physi sorption. Hard cations showed little to no effect on the binding of Pb2+ ions to TiS2. Hard cations affected Cu2+ ion binding to TiS2. Abstract: In the present study, titanium (IV) sulfide (TiS2 ) was synthesized and investigated for the removal of Cu 2+ and Pb 2+ ions from aqueous solutions. TiS2 nanoparticles synthesized through a solvothermal synthesis were characterized using x-ray diffraction (XRD) and scanning electron microscopy (SEM). The average particle size for the TiS2 material was determined to be 8.03 ± 0.98 nm from the diffraction pattern. Studies were performed to examine the effects of pH, temperature, time, and interfering ions on the binding of Cu 2+ and Pb 2+ to the TiS2 . As well isotherm studies were performed to determine the binding capacity of TiS2 for both Cu 2+ and Pb 2+ ions. The pH profile studies showed optimal binding occurred at pH 2 for the sorption of both Cu 2+ and Pb 2+ to the TiS2 . The isotherm studies showed the adsorption capacities at temperatures of 4, 22, and 45 °C for Cu 2+ were 243, 222, and 153 mg/g, respectively. An opposite trend in the adsorption was observed for Pb 2+ binding to the TiS2 . The observed binding capacities for Pb 2+ were 32, 166, and 357 mg/g, at temperatures of 4, 22, and 45 °C, respectively. The thermodynamic parameters for binding showed a non-spontaneous process for the sorption of Cu 2+ whereas a spontaneous binding process was observed for the sorption of Pb 2+ . Additionally, the binding of Cu 2+ on TiS2 in the presence of interfering ions (Na +, K +, Mg 2+, and/or Ca 2+ ) was observed to decrease at high concentrations; however, the binding of Pb 2+ was unaffected by the presence of the same cations.